2015
DOI: 10.1002/jor.23108
|View full text |Cite
|
Sign up to set email alerts
|

Head‐locking durability of fixed and variable angle locking screws under repetitive loading

Abstract: Polyaxial locking screws are increasingly applied in fracture fixation. To investigate the durability of the head-locking mechanism, the removal torque of variable angle (VA) and fixed angle (FA) stainless steel and titanium locking screws was investigated without and after a cyclic loading test. Stainless steel (St) and titanium (Ti) 2.4 mm orthogonally inserted FA screws and 2.4 mm VA screws inserted in different inclinations (0˚-15˚) (n ¼ 6 per group) were locked at 0.8 Nm. Removal torque was determined wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…In the former method, the tightness of the screws is assessed as a prerequisite to maintaining the screw holding power, whereas in the latter approach, the screw holding power required to support the bone under load is utilized. The removal torque tended to be higher than the insertion torque before cyclic loading, 22 although it could be lower afterwards. 23 In the present study, the thread counts for the fully threaded plates were approximately ten, eight, and six, and those for the half-threaded plates were five, four, and three for plate types I, II, and III, respectively.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In the former method, the tightness of the screws is assessed as a prerequisite to maintaining the screw holding power, whereas in the latter approach, the screw holding power required to support the bone under load is utilized. The removal torque tended to be higher than the insertion torque before cyclic loading, 22 although it could be lower afterwards. 23 In the present study, the thread counts for the fully threaded plates were approximately ten, eight, and six, and those for the half-threaded plates were five, four, and three for plate types I, II, and III, respectively.…”
Section: Discussionmentioning
confidence: 82%
“…In the literature, two methods have been used to assess the stability of locking screws. 19 , 21 , 22 The first involved measuring the removal torque of the screws before or after cyclic loading, and the second involved the bending strength of the screws. In the former method, the tightness of the screws is assessed as a prerequisite to maintaining the screw holding power, whereas in the latter approach, the screw holding power required to support the bone under load is utilized.…”
Section: Discussionmentioning
confidence: 99%
“…titanium polyaxial locking screws inserted in different angels, head loosening was not observed after cyclic testing. 15 In this publication 15 authors concluded that screws inserted up to 15 degrees and orthogonally inserted fixed angle locking screws offer a stable locking mechanism. In another study authors concluded that inclination of polyaxial locking screws up to 15 degrees is comparable to orthogonally placed fixed angle locking screws.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, the connection between the screw head and the plate hole was investigated using destructive mechanical tests. 2,4,[13][14][15] In this study, we introduce micro-CT as a novel nondestructive quantitative method investigating locking systems. In this experiment, 3.5 mono-and 3.5 polyaxial locking plates were used.…”
Section: Introductionmentioning
confidence: 99%
“…The harmful effect of off-axis screw insertion has been demonstrated and discussed in previous biomechanical studies. 13,[22][23][24][25] The exclusive failure mode in the present study was cut-out of the 2 proximal screws through cancellous bone. This is reflected by the fact that mechanical failure, defined by abrupt change in the machine and radiological data, was reached significantly earlier than the clinical failure defined by 5 degrees varus tilting of the femoral head.…”
Section: Discussionmentioning
confidence: 99%